1997
DOI: 10.1890/0012-9658(1997)078[1105:cofbb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Frugivory by Bears

Abstract: Abstract. Bears consuming wild fruits for fall energy accumulation are constrained by several factors, including intake rate, the physiological capacity of the gastrointestinal tract, and the metabolic efficiency of gain in body mass. We measured these relationships through foraging and feeding trials using captive and wild black bears (Ursus americanus) and grizzly bears (Ursus arctos). Four fruit types covering a range of sizes and clustering were offered to captive bears to determine the effect of density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(94 citation statements)
references
References 28 publications
6
88
0
Order By: Relevance
“…This supports previous findings that the majority of autumn fat reserves come from carbohydrates from berries (Welch et al 1997). We found that berries constituted 68% of the estimated dietary energy content in autumn, which was intermediate between the 49% reported from northeastern Norway, ca 1100 km north-northeast of our study area (Persson et al 2001) and the 80-81% documented from Jämtland, Sweden, ca 300 km northwest of our study area (Dahle et al 1998).…”
Section: Use Of Berries According To Their Occurrence During Hyperphagiasupporting
confidence: 86%
See 3 more Smart Citations
“…This supports previous findings that the majority of autumn fat reserves come from carbohydrates from berries (Welch et al 1997). We found that berries constituted 68% of the estimated dietary energy content in autumn, which was intermediate between the 49% reported from northeastern Norway, ca 1100 km north-northeast of our study area (Persson et al 2001) and the 80-81% documented from Jämtland, Sweden, ca 300 km northwest of our study area (Dahle et al 1998).…”
Section: Use Of Berries According To Their Occurrence During Hyperphagiasupporting
confidence: 86%
“…During the two years of berry inventory, crowberry showed the greatest concentration of berries (annual means of 458 and 1304 berries m -3 foliage), lingonberry was intermediate (149 and 260), and bilberries showed the lowest concentration (57 and 106). Welch et al (1997) showed experimentally that maximum bite rates of brown bears were depressed when initial fruit density fell to  50 berries m -3 . They conluded that tall, leafy shrubs, such as bilberry in our study, produce fewer, singly spaced berries that are obscured by relatively large leaves, causing bears to search more for and to select individual berries, resulting in lower bite rates and smaller bite sizes.…”
Section: Use Of Berries According To Their Occurrence During Hyperphagiamentioning
confidence: 99%
See 2 more Smart Citations
“…in plant-hummingbird networks [9,17], plant-insect networks [12,18] and plant-frugivore interactions [2]). Foraging constraints are determined by rates of search and handling of, for example, fruits [19], and biochemical constraints are operating if a frugivore is unable to process secondary compounds in fruit pulp. Even a multiple-trait or multiple-constraint model may be needed to make solid predictions about link patterns in real-world networks [20].…”
Section: Introductionmentioning
confidence: 99%